PENDAMPINGAN MEMBUAT STRATEGI PENGUKURAN EVALUASI KEGIATAN PADA ORGANISASI RUANG PUBLIK TERPADU RAMAH ANAK (RPTRA) - Christian, Michael; Rembulan, Glisina Dwinoor (Jurnal Pengabdian dan Kewirausahaan, 2019)
As a place or area of meeting as well as interacting through activities that can be supported in it, the Child Friendly Integrated Public Space (RPTRA) can be explained to have a variety of quite complex work programs that are expected to be implemented well. There are at least 3 (three) aspects of the function of the RPTRA work program that must be implemented, namely services to children, services to the community and disaster services. This study aims to assist the RPTRA management in evaluating which work programs are the top priority that must be carried out. This research involved RPTRA administrators in the Sunter area, North Jakarta. Evaluation assistance is carried out when implementing community service activities with the same topic. The results of this study found that in the aspect of service to children, the performance of making RPTRA as a playground and forum forum for children became a priority indicator of all the existing indicators. Furthermore, in the aspect of service to the community explained that the performance to make RPTRA as a place for complaints of children and women became the main point. In the aspect of disaster services, it is explained that the RPTRA can be used as a container for disaster prevention at any time (for example: floods, fires, and so on). With the limitations of existing research methods, researchers expect further research to explore aspects of other important indicators that are considered by RPTRA administrators in carrying out work programs.